Developing instruments for student performance assessment in physics practicum: A case study of state senior high school of Magelang - Silvia Lutasari; Badrun Kartowagiran (Informascope, 2019)
Assessment of practicum activities has not been performed maximally in which it is limited to unstructured observations without applying assessment instruments and it only covers some skills oriented aspects. For that reason, this research aimed to develop instruments for student performance assessment in physics practicum in State Senior High School of Magelang. This research development study was based on the Borg & Gall model. There were three basic steps followed; Phase 1 (problematization), Phase 2 (product creation), and Phase 3 (product testing) that consists of a limited experiment and a large group experiment. In the study, Aiken formula was used for the validation purposes and the results showed that the instrument had a high degree of content validity with the Alpha coefficient value of 0.948. Based on the Total Variance Explained table, the component column showed that there were six factors representing the variables. Accordingly, the instrument of this research was found feasible to be used for high school student performance assessment in physics practicum.